Robotic Radical Cystectomy: Where are We Today, Where will We be Tomorrow? - Kyle A. Richards; A. Karim Kader; Ashok K. Hemal (The Scientific World Journal)
While open radical cystectomy remains the gold-standard treatment for muscle-invasive bladder cancer and high-risk non–muscle invasive disease, robotic assisted radical cystectomy (RARC) has been gaining popularity over the past decade. The robotic approach has the potential advantages of less intraoperative blood loss, shorter hospital stay, less post-operative narcotic requirement, quicker return of bowel function, and earlier convalescence with an acceptable surgical learning curve for surgeons adept at robotic radical prostatectomy. While short to intermediate term oncologic results from several small RARC series are promising, bladder cancer remains a potentially lethal malignancy necessitating long-term follow-up. This article aims to review the currently published literature, important technical aspects of the operation, oncologic and functional outcomes, and the future direction of RARC.